Cancer Screening Beliefs and Reactions to an Innovative Colorectal Cancer Screening Kit among Chinese Worksite Population - Hou, S.; Chen, P. (Methods of Information in Medicine, 2005)
Objectives: This study assessed the relationships between cancer screening beliefs (perceived pros, cons, and susceptibility) and reactions (acceptance, self-efficacy, intention to purchase) to an innovative home-administered kit (HAK) for fecal occult blood test (FOBT) among Chinese worksite population.Methods: A total of 450 Chinese people aged 40 and older were recruited from ten worksites in Taiwan (2002), with response rate of 83% (375/450).Results: All the belief scales of cancer screening in general showed good internal consistency (Cronbach alphas >0.70). Perceived benefits and barriers to-wards cancer screening were significantly correlated with the acceptance, self-efficacy, and order intention towards the FOBT-HAK (p-values <0.001). Perceived susceptibility of cancer was associated with intention to purchase. After taking gender into consideration, the regression analyses showed similar relationships.Conclusions: Screening beliefs were significantly associated with reactions toward the innovative FOBT-HAK. Intervention programs addressing these beliefs could potentially promote positive reactions to innovative CRC screening strategies.
Keywords: Colorectal neoplasm; screening; occult blood; self efficacy; Chinese